Estudo comparativo das complicações após hipofisectomia endoscópica transesfenoidal primária na reoperação - Leandro Custódio do Amaral (2018)
Background: The treatment of choice in cases of residual or recurrent pituitary adenomas remains undefined. Higher rates of complications and lower rates of success in reoperations due to loss of anatomical landmarks, fibrosis between dissection planes and the effects of previous treatments are still under discussion in the medical literature. Objectives: The primary objective was to compare the complication rates of primary transsphenoidal endoscopic hypophysectomies with those of reoperations. The secondary objective was to identify risk factors associated with higher rates of complications. Methods: The data of 171 patients submitted to endoscopic endonasal transsphenoidal hypophysectomies between 2005 and 2015 were retrospectively reviewed. Out of 183 surgeries, 144 were primary surgeries and 39 were reoperations. Clinical data, visual field tests, imaging and laboratory tests (hormonal profile, anatomopathological and immunohistochemical analyzes) were obtained retrospectively after signing the written informed consent. The surgical complications evaluated were: intraoperative and postoperative cerebrospinal fluid fistulas; meningitis; permanent diabetes insipidus (DI), new deficiencies of the anterior pituitary; deterioration of visual acuity; ophthalmoplegias; campimetric defects; otorhinolaryngological and systemic complications; vascular lesions and death. Sex, age, systemic arterial hypertension, diabetes mellitus, smoking, cardiopathy, use of lumbar drainage and its time of use, invasion of the sphenoid and cavernous sinuses, presence and degree of suprasellar expansion, preoperative pituitary identification, CSF leaks and intraoperative pituitary identification were the variables possibly associated with surgical complications. Results: Intraoperative CSF leaks (p = 0.001), visuals fields changes (p = 0.02) and worsening of visual acuity (p = 0.006) were more common in the group submitted to reoperations. On the other hand, there were no statistically significant differences between the 2 groups in the occurrence of postoperative CSF leaks (p= 0.654), systemic complications (p= 0.249), vascular lesions (p = 0,384), meningitis (p =0.275), rhinologic complications (p= 0.894), DI (p=1,0), anterior pituitary dysfunction (p=0,847), changes in ocular motility (p = 0.629) and mortality (p = 1.0). Intraoperative CSF leak was associated with several complications, such as postoperative fistulas, campimetric losses, deterioration of visual acuity, changes in ocular motility and pituitary dysfunction. The intraoperative pituitary identification was associated with lower incidence of anterior pituitary dysfunction, systemic complications, intraoperative CSF fistulas, permanent DI, new visual field deficits and deteriorating visual acuity. Preoperative pituitary identification did not have the same relevance but was related to reduced risk of postoperative CSF fistulas. Invasion of the cavernous sinus was a risk factor for ophthalmoplegia. The suprasellar expansion was associated to increased the risk of intraoperative CSF fistulas, but showed no statistically significant relationships with new hormonal deficits and visual deterioration. The intraoperative CSF fistulas were associated not only with the postoperative ones, but also with higher rates of hypopituitarism, permanent DI and visual deterioration, involving acuity, ocular motility or campimetric changes. Conclusions: Intraoperative CSF leaks, worsening of visual acuity and new campimetric deficits were more frequent in reoperated patients. Invasion of the cavernous sinus, suprasellar expansion, intraoperative pituitary identification and CSF leaks were important aspects for the occurrence of complications.